Method for the analysis of volatile compounds in virgin olive oil by SPME-GC-MS or SPME-GC-FID - Aparicio-Ruiz, Ramón; Casadei, Enrico; Ortiz-Romero, Clemente; García-González, Diego L.; Servili, Maurizio; Selvaggini, Roberto; Lacoste, Florence; Escobessa, Julien; Vichi, Stefania; Quintanilla-Casas, Beatriz; Tres, Alba; Golay, Pierre-Alain; et al. (MethodsX, 2023)
•A SPME-GC method to determine selected volatile compounds in virgin olive oils was developed and validated.•The method can support the official sensory evaluation of virgin olive oils (Panel test).•Two detectors can be used depending on the technical facilities of the laboratory. During the course of the EU H2020 OLEUM project, a harmonized method was developed to quantify volatile markers of the aroma of virgin olive oil with the aim to support the work of sensory panel test to assess the quality grade. A peer validation of this method has been carried out, with good results in terms of analytical quality parameters. The method allows the quantification of volatile compounds by SPME-GC with two possible detectors, flame ionization detector and mass spectrometry, depending on the technical facilities of the labs applying this method. The method was optimized for the quantification of 18 volatile compounds that were selected as being markers responsible for positive attributes (e.g. fruity) and sensory defects (e.g. rancid and winey-vinegary). The quantification is carried out with calibration curves corrected by the internal standards. Additionally, a protocol is provided to prepare the calibration samples. This procedure enhances reproducibility between labs since one of the main sources of errors is the application of different procedures in calibration. [Display omitted]